2016
DOI: 10.1186/s40463-016-0127-5
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent: do information pamphlets improve post-operative risk-recall in patients undergoing total thyroidectomy: Prospective randomized control study

Abstract: BackgroundInformed consent consists of basic five elements: voluntarism, capacity, disclosure, understanding, and ultimate decision-making. Physician disclosure, patient understanding, and information retention are all essential in the doctor-patient relationship. This is inclusive of helping patients make and manage their decisions and expectations better and also to deal with any consequences and/or complications that arise. This study investigates whether giving patients procedure-specific handouts pre-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 13 publications
0
48
1
Order By: Relevance
“…We selected 34 trials with 3742 participants, of which 29 were randomised, controlled , 4 were quasi‐randomised and 1 was cluster‐randomised (Figs. and ; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected 34 trials with 3742 participants, of which 29 were randomised, controlled , 4 were quasi‐randomised and 1 was cluster‐randomised (Figs. and ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with an inadequate understanding of the language used to transmit information were not studied in these trials. The effects of different information formats were tested by 30 trials and different timings by 5 trials .…”
Section: Resultsmentioning
confidence: 99%
“…Providing preparatory information before invasive medical procedures could be effective in reducing patients' anxiety and complaints and enhancing the success of treatment in many medical specialties [27,28]. It has also been shown that providing information to patients can help dentally anxious people prepare for treatment and in turn this reduces anxiety levels.…”
Section: [Irena] a Root Canal Sounds Like A Very Fearful Thing And Somentioning
confidence: 99%
“…Many different methods for improving patient education have been tried using written information (such as brochures or pamphlets written at a grade‐level equivalent) and standardized audio or video recording and interactive web pages with mixed results. While some studies found that providing visual or written information can increase percentage of retained information from 20% to 50%, a recent randomized controlled trial by Alsaffar et al . failed to show any significant improvement in written recall questionnaire among patients that received surgical information pamphlet prior to their thyroidectomies compared to controls.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, the surveys used during the study to test patient's recall were custom designed and are not validated, peer‐reviewed surveys to test recall and satisfaction. However, our questionnaires were based on similar studies published in the literature . Second, we were not able to achieve significance when assessing overall recall and subgroup analyses focusing on the number of video views to recall risk were not possible due to a higher dropout rate than anticipated.…”
Section: Discussionmentioning
confidence: 99%